Derivation and characterisation of a conditionally immortal mouse mammary epithelial cell line using a transgenic approach - Gordon, Katrina Ellen (The University of Edinburgh, 1997)
The induction of proliferation and differentiation in mammary epithelium during pregnancy is quite remarkable and results in the synthesis of copious amounts of milk at parturition to feed the offspring. Understanding the key factors involved in the tissue- specific activation of the milk protein genes and their relationship to tissue organisation have been important areas of mammary gland research. Epithelial cell lines can provide invitro model systems in which both the growth and differentiation of the epithelium can be investigated under defined conditions. This thesis describes the isolation and characterisation of a conditionally immortalised mouse mammary epithelial cell line. The approach adopted utilised transgenic mice harbouring an enhancerless thermolabile mutant of SV40 T-antigen (tsA58) construct driven by the ovine (3-lactoglobulin (BLG) milk protein gene promoter as a source of mammary cells. It was envisaged that the expression of T-antigen would be limited to the secretory epithelium of the mammary gland and its immortalising properties active only at the permissive temperature of 33°C. However several of the founder mice developed tumours at ectopic sites due to leaky expression of T-antigen from the BLG promoter. Mammary tissue from the five surviving transgenic lines of mice were used to generate mammary cultures. A novel isolation procedure, exploiting the ability of explant cultures to generate epithelial outgrowths, was used. One cell line, designated KIM-2, isolated from the lowest copy transgenic line at a semi-permissive temperature of 37°C was characterised further. These cultures, established from midpregnant glands, are highly enriched with luminal cells as assessed by their strong positive staining with secretory epithelial markers (keratins 18 and 19) and have retained a stable phenotype for over 60 passages. Investigation into the functional differentiation of KIM-2 cells has shown that the induction of (3-casein is similar to existing mammary cell models. However the KIM-2 cell line has retained the ability to express a late differentiation marker, whey acidic protein (WAP) on plastic unlike other cell lines which require quite complex culture conditions to induce further differentiation. Initial transfection studies in this cell line with foreign DNA constructs has also proven to be successful. Therefore, the KIM-2 cell line has the potential to provide a good in vitro model to study factors involved in mammary epithelium development.
The derivation and characterisation of a conditionally immortal mouse mammary epithelial cell line using a transgenic approach